Psychological Factors Shaping Women Management Graduates' Entrepreneurial Intention (Patan Pragya, 2025)
The study aims to assess the psychological factors that determine the intention of management graduates towards entrepreneurial activities. This study adopts a positivist research paradigm with a descriptive and causal research methodology that highlights the impact of psychological factors as antecedents of theory of planned behavior to justify the intention of management graduates towards entrepreneurship. A sample of 401 respondents was collected using purposive sampling method from the respondents in study area. The factors that have been taken to study the mindset of management graduates trying to progress as entrepreneurs in their career have been deeply studied. Variables of Theory of Planned Behavior (TPB) such as subjective norms, attitude and perceived behavioral control of management graduates towards entrepreneurship. The result indicates that perceived behavioral control of graduates is the most important influential factors. Policymakers need to focus on increasing the access of graduates towards more exposure and skill development and present themselves well in the market. To achieve the required development and perseverance of a young graduate towards entrepreneurship, graduates should focus on learning new skills, being active, enthusiastic, open to new opportunities and curious to acquire knowledge. Thus, educating, polishing and provision of exposure to young talents and graduates can surely evolve the interest of young enthusiasts towards entrepreneurial activities.